PENANGGULANGAN KEJAHATAN PENCURIAN AKIBAT KECANDUAN JUDI SLOT ONLINE: TINJAUAN YURIDIS KRIMINOLOGIS - Soraya, Joice; Ansy Althafzufar, Muhammad (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2024)
The increasing prevalence of online slot gambling has led to a rise in theft committed by gambling addicts in order to obtain money for gambling This study aims to examine this phenomenon from a legal and criminological perspective and formulate measures to address it. The method used is normative legal research through literature study with a legislative and conceptual approach. The research results indicate that the main contributing factor is online slot gambling addiction, which leads individuals to justify any means, including theft, in order to obtain money From a legal perspective, theft with such motives can be prosecuted under Article 362 of the Criminal Code, which carries a maximum prison sentence of 5 years However, legal prosecution alone is not sufficient to address the root of the problem. Therefore, recommended measures for handling this issue include: 1) The government needs to strictly regulate and limit online gambling; 2) Collaboration among various parties is necessary to educate the public about the dangers of online gambling; 3) Rehabilitating gambling addicts so they can break free from their addiction; 4) Empowering them economically to prevent them from resorting to theft With these comprehensive steps, it is hoped that theft crimes resulting from online slot gambling addiction can be effectively addressed. Keywords: Criminology, Online Slot Gambling, Theft.